Single dose high-dose-rate brachytherapy with focal dose escalation for prostate cancer: Mature results of a phase 2 clinical trial. (June 2021) - Armstrong, Shreya; Brown, Stephanie; Stancliffe, May; Ostler, Peter; Hughes, Robert; Hoskin, Peter; Alonzi, Roberto
Highlights: 50 patients received single fraction high-dose-rate brachytherapy (HDR-BT) for localised prostate cancer, with dose escalation to the dominant intraprostatic nodule (DIL) to 21 Gy and two de-escalation schedules to the remaining prostate. With a median follow up of 70.6 months, 15 patients developed biochemical failure, including 8 in the group that received minor dose de-escalation to the non-DIL prostate (group 1) and 7 in the group that received moderate de-escalation (group 2). Five-year biochemical no evidence of disease (bNED) was 88% in group 1 and 76% in group 2 ( p = 0.05). Overall 5-year freedom from local failure (FFLF) was 96% in group 1 and 84% in group 2 ( p = 0.03). No acute ≥G3 genitourinary or ≥G2 gastrointestinal toxicity was reported. The median IIEF decreased in the first 6 months improving to a peak median score of 20 at 54 months. Focal boost to the DIL did not improve biochemical or local control compared to contemporary reports of 19 Gy single fraction treatment to the whole gland. HDR-BT as monotherapy should be undertaken using a minimum of 2 fractions. Abstract: Aim: The dominant intraprostatic lesion (DIL) is the commonest site of relapse after single dose high-dose-rate brachytherapy (HDR-BT) for localised prostate cancer. This study investigated toxicity and clinical outcomes of focal dose escalation to the DIL with dose de-escalation to the remaining prostate. Materials/Methods: Between November 2012 and July 2016, 50 patients with localised prostate adenocarcinoma received single fraction HDR-BT. 21 Gy was prescribed to the DIL, with two de-escalation prescription schedules for the remaining prostate. Primary outcomes included biochemical no evidence of disease (bNED), local recurrence free survival (LRFS), and metastasis free survival (MFS). Secondary outcomes included late genitourinary, gastrointestinal and sexual toxicity. Kaplan—Meier analyses with log rank tests were used to estimate bNED, LRFS and MFS. Results: With a median follow up of 70.6 months, 15 patients developed biochemical failure, including 8 in the group that received minor dose de-escalation to the non-DIL prostate (group 1) and 7 in the group that received moderate de-escalation (group 2). Five-year bNED was 88% in group 1 and 76% in group 2 ( p  = 0.05). Overall 4-year and 5-year FFLF in group 1 was 100% and 96% and in group 2 92% and 84%. These differences were statistically significant ( p  = 0.03). No acute ≥G3 genitourinary or ≥G2 gastrointestinal toxicity was reported. The median IIEF decreased in the first 6 months improving to a peak median score of 20 at 54 months. Conclusion: Focal boost to the DIL did not improve biochemical or local control after single-fraction HDR monotherapy compared to what would be expected from 19 Gy single fraction treatment to the whole gland.